BIOMECHANICS OF RUNNING STEP TECHNIQUE - Umarov Abdusamat Abdumalikovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article deals with the study of the change in the movements of the leg links when running on a turn, respectively, increased centrifugal force and shortened step. Analysis of angular indicators of running technique by static processing angular characteristics of running poses.